(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
The purposes of this research are to find out the effective start simple story (SSS) in improving students’ reading narrative text and to find out the the students’ perceptions about usage the Start Simple Story (SSS) to improve reading narrative. It was conducted at Class VIII-B of SMP Kartika XX-2 Makassar which consisted of 20 students’ as the sample of the research. This research used quantitative approach with pre-experimental research using pre-test and post-test. The researcher used two research instruments. There were tests and questionnaire. The research findings indicated that Using start simple story (SSS) method in improving the students’ reading narrative text. It was proved by the mean score of pre-test was 62 is classified as fairly good score then improved to be 80 in post-test is classified as very good. The improvement percentage was 25, 806%. It means that there was a significant difference of achievement in the test result before and after applying this method. The result of the questionnaire proved that most of the students were interested in using start simple story (SSS) method.